TINJAUAN KEBUTUHAN TENAGA PEREKAM MEDIS BERDASARKAN BEBAN KERJA DI UNIT FILLING RAWAT INAP PADA RUMAH SAKIT DR. HAFIDZ CIANJUR - hakim, Luqman Nul; Sanusi, Najmi Ahmad Najmuddin (Jurnal TEDC; Vol 19 No 1 (2025): JURNAL TEDCDO - 10.70428/tedc.v19i1.1184, 2025)
Health is a state of complete physical, mental and social well-being, and not just the absence of disease or disability. A hospital is a public facility owned by the government or private sector which has a role in efforts to improve public health services, this effort is assisted by the presence of a workforce. The availability of quality health workers in sufficient numbers is very important for health development in the region to achieve the goal of better health development. The quality of hospital services can be determined from the level of patient satisfaction. Patient satisfaction is determined by the overall services provided and carried out by the workforce. This scientific activity aims to determine the standard requirements for medical recording personnel based on the workload in the inpatient filing unit at Dr. Hafidz Cianjur Hospital. The benefit of this scientific activity is that it provides suggestions for improving the quality of health services at Dr. Hafidz Cianjur Hospital and becomes a reference for institutions. This scientific activity uses an analysis method using WISN (Workload Indicator Staffing Need). The result of this scientific activity is that according to WISN, Dr. Hafidz Cianjur Hospital still lacks medical personnel, especially in the medical record filling unit, with the number of shortages according to WISN's calculations being 1 person.